2021
DOI: 10.2147/idr.s326148
|View full text |Cite
|
Sign up to set email alerts
|

Methicillin-Resistant Staphylococcus aureus Nasal Colonization Among Health Care Workers of a Tertiary Hospital in Ecuador and Associated Risk Factors

Abstract: Background Methicillin-resistant Staphylococcus aureus (MRSA) is resistant to most of the commonly used antibiotics and is therefore a public health issue. Colonization with MRSA is a risk factor for infection or transmission. Purpose To determine the prevalence of colonization with Staphylococcus aureus (SA) and MRSA strains in health care workers (HCWs) at a tertiary hospital in Ecuador and to determine the risk fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
7
1
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 43 publications
7
7
1
3
Order By: Relevance
“…Several studies have reported rates of nasal carriage of MRSA among healthcare staff ranging from 5.2%-25.5% 7,8,9 . Our rate of 23.2% S.aureus and 4% MRSA is comparable to Baroja et al,2021 from Ecuador 10 . A study from south India has reported prevalence rate of 19.7% of S.aureus nasal colonization in 2 nd year students, who had started clinical postings with MRSA rate of 11.1% 11 .…”
Section: Resultssupporting
confidence: 90%
“…Several studies have reported rates of nasal carriage of MRSA among healthcare staff ranging from 5.2%-25.5% 7,8,9 . Our rate of 23.2% S.aureus and 4% MRSA is comparable to Baroja et al,2021 from Ecuador 10 . A study from south India has reported prevalence rate of 19.7% of S.aureus nasal colonization in 2 nd year students, who had started clinical postings with MRSA rate of 11.1% 11 .…”
Section: Resultssupporting
confidence: 90%
“…Our results were nearly similar to many previous studies. 15,16,17 Relatively low carriage rate if compared with Gomes et al 18 and Elzorkany et al 19 who found that frequency was 33%, 37.2% among HCWs and higher than Baroja et al 15 who observed that MRSA carriage rate among HCWs was 5%. These variances in MRSA prevalence may be due to differences in measures of infection control applied in each hospital, frequency of antibiotic use, the method of MRSA detection and its sensitivity, and the characters of the studied population Jaradat et al 20 .…”
Section: Discussionmentioning
confidence: 92%
“…Drug-resistant pathogens continue to be an important and growing threat to human health and economic development ( 1 3 ). The Centers for Disease Control and Prevention estimated that more than 70% of bacteria causing nosocomial infections are resistant to at least one of the drugs commonly used for treating these infections ( 4 ). According to a study chaired by Jim O’Neill, drug-resistant diseases cause more than 700,000 deaths/year ( 5 ).…”
Section: Introductionmentioning
confidence: 99%